Delta-Globin Gene Expression Is Enhanced in vivo by Interferon Type I - Manchinu, Maria Francesca; Simbula, Michela; Caria, Cristian Antonio; Musu, Ester; Perseu, Lucia; Porcu, Susanna; Steri, Maristella; Poddie, Daniela; Frau, Jessica; Cocco, Eleonora; Manunza, Laura; Barella, Susanna; et al. (Frontiers in Medicine, 2020)
Beta hemoglobinopathies are widely spread monogenic lethal diseases. Delta-globin gene activation has been proposed as a possible approach to cure these pathologies. The therapeutic potential of the delta-globin, the non-alpha component of Hemoglobin A2 (α2δ2; HbA2), has been demonstrated in a mouse model of beta thalassemia while its anti-sickling effect, comparable to that of the gamma globin, has been established some time ago. Here we show that delta-globin gene expression is considerably increased in a DeoxyribonucleaseII-aplha knockout mouse model in which type 1 Interferon (Interferon beta, IFNb) is activated. IFNb activation in the fetal improves delta-globin gene expression while beta-globin gene expression is significantly reduced. In addition, we show that HbA2 is significantly increased in patients with multiple sclerosis under type 1 Interferon treatment. Our results represent a proof of principle that delta-globin expression could be enhanced through the use of molecules. This observation is potentially interesting in view of a pharmacological approach able to increase HbA2 level.